The Trials of Masculinity: Policing Sexual Boundaries, 1870-1930 - Dummitt, Chris (Labour / Le Travail, 1999)
The article reviews the book, "The Trials of Masculinity: Policing Sexual Boundaries, 1870-1930," by Angus McLaren.